The manufacturing and the application of polycrystalline diamond tools – A comprehensive review. (August 2020) - Li, Guangxian; Rahim, Mohammad Zulafif; Pan, Wencheng; Wen, Cuie; Ding, Songlin
Abstract: Advanced materials such as titanium alloys and metal matrix composites are extensively used in the aerospace industry and biomedical engineering. They are difficult to machine because of the severe abrasion and high temperature at the tool/chip and tool/workpiece interfaces which cause severe tool wear and premature tool rejection. Compared with conventional cutting tools, polycrystalline diamond (PCD) tools are promising in machining refractory metals and hard-to-machine materials because of the outstanding mechanical properties of PCD. This paper reviewed the manufacturing and application of PCD cutting tools. The researches on manufacturing process of PCD tools and the application in cutting hard-to-machine materials were analysed, and the results and findings were comprehensively discussed. Two most widely used refining methods including abrasive grinding and electrical discharge grinding (EDG) as well as the defects caused by the processes were presented. The wear process of PCD tools in different industrial cutting methods and the wear mechanism of different PCD materials were explained in both micro-scale and macro-scale. Research directions and the trend of the application of PCD cutting tools were introduced.